- TINJAUAN YURIDIS PENERAPAN PRESENSI ONLINE PADA MASA PANDEMI COVID-19 DENGAN PEMBERLAKUAN SE-15/BC/2020 DI LINGKUNGAN KANTOR PUSAT DIREKTORAT JENDERAL BEA DAN CUKAI KEMENTERIAN KEUANGAN: - - Guzthaviany Valmaira Nasya; Purnomowati, Reni Dwi (Faculty of Law, Universitas Trisakti, 2023)
Since the tools are manual and can transmit between people when used simultaneously with fingerprint trackers, online presence is a mechanism that is used to stop the Covid-19 virus from spreading. Formulation of the issue; how to use online presence in the Directorate General of Customs and Excise, Ministry of Finance, in accordance with the hierarchy of laws and regulations during the COVID-19 pandemic; and arrangements for enforcing sanctions if they violate the rules regarding working hours for civil servants in the Directorate General of Customs and Excise, Ministry of Finance. This article is normative juridical method is the research methodology. The main data source consists of the outcomes of interviews The results of the research were analyzed qualitatively and conclusions used deductive logic. Research results and discussion as well as conclusions; first, the online attendance of the Director General of Customs and Excise was held based on SE-15/BC/2020 which is in accordance with the Minister of Finance Regulation Number 221/PMK.01/2021 where there is an obligation for civil servants to comply with civil servant discipline regulated in the Government Regulation on Civil Servant Discipline which is a follow-up rule from the State Civil Apparatus Law.